Identifikace a analýza důvodů neúčasti pacientů ve screeningu karcinomu plic pomocí nízkodávkové výpočetní tomografie - Janeček, Jiří; Jiří Janeček (České vysoké učení technické v Praze, 2024)
Cílem práce je identifikovat a analyzovat důvody, které vedou pacienty, vhodné ke screeningu karcinomu plic k odmítnutí participace a účasti v programu. Pilotní program časného záchytu karcinomu plic se po více než roce svého fungování potýká s vysokou mírou noncompliance oslovených vysoce rizikových pacientů. Počet provedených LDCT vyšetření, oslovených a účastnících se pacientů se zcela zásadně liší od původně stanovených cílů a projekce vývoje programu. Data získaná dotazníkovým šetřením byla zpracována pomocí metod kořenové analýzy. Zjištěné závěry jsou takové, že primárním důvodem neúčasti a odmítnutí účasti zapojeni do screeningu jsou subjektivní pocity zdraví, podcenění rizika a obavy a strach.

The aim of this study is to identify and analyze the reasons that lead patients eligible for lung cancer screening to refuse to participate and participate in the program. After more than a year of operation, the pilot early lung cancer screening program is experiencing high rates of noncompliance among high-risk patients approached. The number of LDCT examinations performed, patients approached and participating is quite different from the original goals and projections for the development of the program. Data obtained from the questionnaire survey were processed using root cause analysis methods. The findings are that the primary reasons for non-participation and refusal to engage in screening are subjective feelings of health, underestimation of risk and worry and fear.
Identification and Analysis of Patients' Reasons for Not Participating in Low-dose Computed Tomography Lung Cancer Screening
Keywords: pilotní program; screening; karcinom plic; nízkodávkové CT; neúčast; pilot program; screening; lung cancer; low-dose CT; non-participation